Electrolyte for ternary positive electrode secondary battery and secondary battery
By using an electrolyte formula containing vinyl carbonate, ethyl propionate, lithium salt, silicone additive and lithium acesulfame in lithium-ion batteries, the problem of oxidation and decomposition of traditional electrolytes at high voltage is solved, and the battery is high cycle stability and thermal safety is achieved.
Patent Information
- Application Number
- CN202411913660.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
When increasing the energy density and charging voltage of lithium-ion batteries, traditional carbonate electrolytes are prone to oxidation and decomposition at high voltages, resulting in a shortened battery life and an increased risk of thermal runaway.
An electrolyte formulation including vinyl carbonate, ethyl propionate, lithium salt, silicone additive and lithium acesulfame is used, which is suitable for nickel-cobalt-manganese ternary lithium batteries, ensuring the cell cycle stability and capacity retention rate under a high charging voltage of 4.5V to 4.8V.
It significantly improves the cycle stability and capacity retention rate of the battery under high charging voltage, extends the service life of the battery, suppresses adverse reactions between the positive electrode and the electrolyte, reduces the risk of thermal runaway, and improves the thermal safety of the battery.
Smart Images

Figure BDA0005206342090000041 
Figure BDA0005206342090000051 
Figure BDA0005206342090000061
Abstract
Description
Technical Field
[0001] The invention relates to the field of new energy, in particular to an electrolyte for a ternary positive electrode secondary battery. Background Art
[0002] Since the commercialization of lithium-ion batteries, with its significant advantages such as high energy density, long cycle life and environmental friendliness, it has become the preferred technology in the field of chemical energy storage batteries and is widely used in multiple markets such as electronic products and new energy electric vehicles. With the rapid development of new energy vehicles, especially pure electric vehicles, the requirements for the performance of lithium-ion batteries are increasing day by day.
[0003] Increasing the operating voltage of the battery is one of the ways to increase the energy density. Currently, there are many high-voltage cathode materials with voltages exceeding 4.5V (such as lithium cobalt phosphate and lithium nickel manganese oxide). When the voltage exceeds 4.3V, the traditional carbonate electrolyte will undergo oxidative decomposition and produce a chemical reaction with the cathode material, which seriously affects the battery life.
[0004] The fast charging technology of batteries used in new energy vehicles has also put forward new requirements. In order to further improve the fast charging performance of batteries, EP materials with lower viscosity and higher conductivity have been selected to partially replace traditional carbonate solvents. This method reduces the viscosity of the electrolyte and improves the conductivity of lithium ions. There is also an increase in the use of lithium salts, thereby further enhancing the conductivity of lithium ions.
[0005] The present invention proposes a new electrolyte and a secondary battery using the electrolyte in order to improve the battery energy density and the charging voltage. Summary of the invention
[0006] The present invention claims protection for an electrolyte with high voltage stability, which is used for a secondary battery whose positive electrode active material is LiNixCoyMnzO2, wherein x, y, z represent the molar fractions of nickel, cobalt, and manganese, respectively, and x+y+z=1, and the electrolyte includes carbonate, ethyl propionate, lithium salt, and also includes an organic silicon additive and a lithium acesulfame additive.
[0007] Furthermore, the carbonate is a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC), and the mass ratio of EC to EMC is 3-4:7-6.
[0008] Furthermore, the mass ratio of ethyl propionate in the electrolyte is 1-2%.
[0009] Furthermore, the lithium salt is LiPF6, and its mass fraction in the electrolyte is 13% to 15%.
[0010] Furthermore, the organosilicon additive is 1,3-divinyltetramethyldisiloxane (DTMS), and its mass fraction in the electrolyte is 0.1% to 0.5%.
[0011] Furthermore, the mass fraction of the lithium acesulfame in the electrolyte is 0.1% to 1%.
[0012] Furthermore, the electrolyte also meets the following conditions: the electrolyte is suitable for nickel-cobalt-manganese ternary lithium batteries with a charging voltage of 4.5V to 4.8V.
[0013] Furthermore, the positive electrode active material of the secondary battery is NCM811.
[0014] Furthermore, the injection coefficient of the electrolyte is 3.15-3.5 g / Ah.
[0015] A secondary battery comprising:
[0016] A positive electrode, the positive electrode comprising an active material LiNixCoyMnzO2, wherein x, y, z represent the molar fractions of nickel, cobalt, and manganese, respectively, and x+y+z=1;
[0017] A negative electrode comprising an active material, graphite;
[0018] Electrolyte,
[0019] The secondary battery has good cycle stability and capacity retention rate when the charging voltage is 4.5V to 4.8V.
[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0021] The electrolyte of the present invention significantly improves the cycle stability and capacity retention rate of the battery at a high charging voltage of 4.5V to 4.8V, thereby extending the service life of the battery.
[0022] The adverse reaction between the positive electrode and the electrolyte is suppressed, the risk of thermal runaway of the battery is reduced, and the thermal safety of the battery is improved. The cycle life and capacity retention rate of the battery are improved, so that the battery can maintain a high capacity and efficiency during long-term use, reducing the cost and use cost of the battery. DETAILED DESCRIPTION
[0023] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0024] High charging voltage is of great significance and value in secondary battery technology. It plays an important role in improving the energy density of batteries and accelerating charging speed.
[0025] An increase in charging voltage means that the battery can store more electrical energy. Under the same conditions, increasing the charging voltage can allow the battery to transfer more charge during the charging and discharging process, thereby increasing the battery's capacity. A high charging voltage can more effectively utilize the activity of the battery's positive and negative electrode materials, allowing the materials to react more fully during the charging and discharging process, thereby increasing the battery's energy density.
[0026] For applications such as electric vehicles, driving range is one of the important indicators for evaluating their performance. Increasing the charging voltage can significantly increase the driving range of electric vehicles, allowing electric vehicles to travel farther on a single charge, thereby meeting the needs of more users.
[0027] A high charging voltage can make the battery have a higher power output capacity during the charging and discharging process, meeting the needs of fast charging and discharging. In a low temperature environment, the charging and discharging performance of the battery is usually affected. Increasing the charging voltage can improve the performance of the battery in a low temperature environment to a certain extent.
[0028] High voltage requires several factors, and the requirements for electrolyte are particularly prominent. Generally speaking, a variety of additives are used to form an excellent electrolyte that can be used for high voltage.
[0029] Silicone is composed of a highly cross-linked network structure, the main chain is composed of Si-O bonds, and the side chain can introduce other organic functional groups to make its structure diverse. Due to its ideal dielectric constant, polarity, heat resistance and chemical resistance, silicone shows good application potential in lithium-ion electrolytes. It can be used in liquid electrolytes as an additive or solvent, and can also be used in solid electrolytes or condensed polymer electrolytes as a polymer host, thereby improving the performance of lithium-ion battery electrolytes.
[0030] 1,3-Divinyltetramethyldisiloxane (DTMS) is a multifunctional additive. This additive is used to improve the cycle stability and capacity retention of lithium-rich manganese-based layered oxide cathodes (LRMs). Studies have found that DTMS can significantly increase the capacity retention of LRM / Li batteries from 42.8% to 75% at 0.5C. Physical characterization results show that DTMS reacts with HF / F- in the electrolyte to produce a layer on the LRM surface that is less resistant and thinner than the LRM. The DTMS-derived layer suppresses adverse reactions between the positive electrode and the electrolyte, thereby effectively maintaining the positive electrode structure.
[0031] Acesulfame salt has been found to improve the cycle life of lithium secondary batteries. The anion structure of acesulfame is as follows:
[0032]
[0033] In the present invention, the inventors used a new electrolyte solution:
[0034] The configuration mass ratio is ethylene carbonate (EC): ethyl methyl carbonate (EMC): ethyl propionate (EP)
[0035] =3-4:7-6:1-2 solution, LiPF6, organic silicon additive (1,3-divinyltetramethyldisiloxane) and lithium acesulfame are dissolved in the solvent. After preparing the electrode solution, a secondary battery is prepared.
[0036] Cathode sheet preparation
[0037] The positive electrode active material is a nickel-cobalt-manganese ternary positive electrode material with a chemical formula of LiNixCoyMnzO2, where x, y, and z represent the molar fractions of nickel, cobalt, and manganese, respectively, and x+y+z=1. The ratio of the nickel-cobalt-manganese ternary positive electrode material used is NCM811 (8:1:1).
[0038] Mixed slurry: The positive electrode active material, the binder and the conductive agent are mixed in a mass ratio of 97.2:1.1:1.1:0.6, and fully stirred with N-methylpyrrolidone under a vacuum environment.
[0039] Coating: The positive electrode active slurry is coated on the surface of the current collector by conventional methods and then rolled.
[0040] Drying: The coated current collector is placed in a drying oven below 100°C to dry the current collector to a moisture content of less than 200 ppm.
[0041] Slitting: According to the design requirements of the battery core, the aluminum foil is cut into positive electrode sheets of the required size.
[0042] Negative electrode preparation
[0043] Mixed slurry: Using deionized water as solvent, the negative electrode active material graphite, conductive agent (conductive carbon black and CNT), sodium carboxymethyl cellulose and binder are mixed evenly in a mass ratio of 96:1:1:1:1 and stirred thoroughly.
[0044] Coating: Evenly coat the negative electrode slurry on the surface of the current collector, and roll and dry it.
[0045] Drying: The coated current collector is placed in a drying oven below 100°C to dry the current collector to a moisture content of less than 200 ppm.
[0046] Battery preparation
[0047] Winding: The positive electrode sheet, separator and negative electrode sheet are prepared into a soft-pack wound battery with a nominal capacity of 5Ah.
[0048] Injection: The injection coefficient of the electrolyte is 3.15-3.5g / Ah.
[0049] Then pre-charging, formation, aging, and constant capacity are carried out.
[0050] In the present invention, the specific formula of the electrolyte is:
[0051]
[0052]
[0053] The electrolyte with the above formula and NCM811 (8:1:1) positive electrode were selected to make 5 soft-pack batteries and test them.
[0054] 1. Sample Preparation
[0055] According to the above electrolyte formula (No. 1-15), 5 soft pack batteries were made for each formula, totaling 75 battery samples. All batteries used NCM811 (8:1:1) positive electrode material to ensure the consistency of the positive electrode material.
[0056] 1.1 Electrolyte configuration
[0057] The electrolyte preparation process requires precise control of the mass ratio of each component to ensure the consistency of each formula. The specific steps are as follows:
[0058] Using a high-precision electronic balance, ethylene carbonate (EC), ethyl methyl carbonate (EMC), ethyl propionate (EP), LiPF6, an organosilicon additive (1,3-divinyltetramethyldisiloxane) and lithium acesulfame were weighed respectively according to the mass ratio specified in the formula.
[0059] Add the weighed solid materials (LiPF6, silicone additives, lithium acesulfame) to an appropriate amount of solvent (EC, EMC, EP), and stir thoroughly at an appropriate temperature using a magnetic stirrer until all the solid materials are completely dissolved.
[0060] The dissolved electrolyte is filtered using a suitable filter to remove possible impurities and insoluble matter.
[0061] Dispense the filtered electrolyte into clean, dry containers and label them with the formula number and preparation date.
[0062] 1.2 Preparation of positive electrode
[0063] The preparation process of the positive electrode sheet includes the steps of mixing slurry, coating, drying and slitting. The specific method is as follows:
[0064] The positive electrode active material (NCM811, nickel-cobalt-manganese ternary positive electrode material), binder (such as polyvinylidene fluoride PVDF), and conductive agent (such as carbon black, carbon nanotube CNT) are mixed in a mass ratio of 97.2:1.1:1.1:0.6, and an appropriate amount of N-methylpyrrolidone (NMP) is added as a solvent. Under a vacuum environment, a planetary mixer is used to fully stir until a uniform positive electrode slurry is formed.
[0065] Evenly coat the positive electrode slurry on the surface of the current collector (such as aluminum foil) and use a scraper to control the coating thickness. During the coating process, be careful to avoid bubbles and uneven coating.
[0066] Place the coated current collector in a drying oven and dry it at a temperature below 100°C until the moisture content is less than 200ppm. During the drying process, pay attention to controlling the temperature and time to avoid thermal decomposition or oxidation of the positive electrode material.
[0067] According to the design requirements of the battery core, use a slitting machine to cut the dried aluminum foil into positive electrode sheets of the required size. During the slitting process, pay attention to maintaining the flatness of the positive electrode sheets and the neatness of the edges.
[0068] 1.3 Negative electrode preparation
[0069] The preparation process of the negative electrode sheet is similar to that of the positive electrode sheet, including steps such as mixing slurry, coating, and drying.
[0070] The specific method is as follows:
[0071] Using deionized water as solvent, the negative electrode active material (graphite), conductive agent (conductive carbon black and CNT), sodium carboxymethyl cellulose (CMC) and binder (such as styrene-butadiene rubber SBR) are mixed uniformly at a mass ratio of 96:1:1:1:1. A stirrer is used to fully stir until a uniform negative electrode slurry is formed.
[0072] The negative electrode slurry is evenly coated on the surface of the current collector (such as copper foil), and the coating thickness is controlled by a scraper. During the coating process, care should be taken to avoid bubbles and uneven coating.
[0073] Place the coated current collector in a drying oven and dry it at a temperature below 100°C until the moisture content is less than 200ppm. During the drying process, pay attention to controlling the temperature and time to avoid thermal decomposition or oxidation of the negative electrode material.
[0074] The dried negative electrode sheet is rolled to improve its density and conductivity. During the rolling process, the pressure and speed should be controlled to avoid damage or deformation of the negative electrode sheet.
[0075] 1.4 Battery Assembly
[0076] The prepared positive electrode sheet, negative electrode sheet and separator are wound into a battery cell in a certain order, and then the electrolyte is injected and sealed to form a soft pack battery. The specific steps are as follows:
[0077] The positive electrode sheet, separator and negative electrode sheet are stacked in sequence and wound into a battery cell using a winding machine. During the winding process, attention should be paid to controlling the winding tension and speed to avoid gaps or short circuits inside the battery cell.
[0078] According to the capacity of the battery cell and the electrolyte injection coefficient (3.15-3.5g / Ah), calculate the required amount of electrolyte and inject it into the battery cell. During the injection process, pay attention to controlling the injection speed and pressure to avoid electrolyte overflow or bubbles in the battery cell.
[0079] The battery cell after liquid injection is sealed to form a complete soft pack battery. During the sealing process, attention should be paid to controlling the sealing temperature and pressure to ensure good sealing performance of the battery cell.
[0080] The assembled soft-pack battery is pre-charged to activate the chemical reaction inside the battery and stabilize the battery performance. During the pre-charging process, it is important to control the charging current and voltage to avoid overcharging or thermal runaway of the battery.
[0081] The pre-charged soft-pack battery is subjected to formation treatment to further improve the performance and stability of the battery. During the formation process, it is important to control the formation current and time to ensure that a stable SEI film is formed inside the battery.
[0082] The formed soft-pack batteries are placed under certain temperature and humidity conditions for aging treatment to further stabilize battery performance and screen out defective products. During the aging process, it is important to control the temperature and humidity conditions as well as the aging time.
[0083] The aged soft-pack battery is subjected to constant capacity treatment to determine its actual capacity and performance parameters. During the constant capacity process, attention should be paid to controlling the discharge current and time as well as the discharge termination voltage and other parameters.
[0084] Test charging voltage selection 4.5V, 4.6V, 4.7V, 4.8V.
[0085] The test selected a high-precision charge and discharge test system to accurately control the charging voltage and current. The temperature monitoring system, including an infrared thermal imager and a built-in temperature sensor, monitors the surface and internal temperature of the battery in real time. Safety protection devices, such as explosion-proof boxes and emergency power-off systems, ensure safety during the test. Data acquisition and analysis software is used to record and analyze test data.
[0086] The test environment temperature is controlled at 25±5℃ and the humidity is maintained at RH 30%-70% to reduce the interference of external environmental factors. Ensure that the test area is well ventilated.
[0087] The test method is:
[0088] 1. Basic performance test:
[0089] Under standard charging conditions (4.2V), all batteries were tested for initial capacity and the initial capacity of each battery was recorded as a benchmark.
[0090] Conduct internal resistance test to evaluate the internal conductivity of the battery.
[0091] Charging voltage gradient test:
[0092] The batteries are divided into 5 groups, each with 15 batteries, corresponding to charging voltages of 4.5V, 4.6V, 4.7V, and 4.8V respectively.
[0093] At each charging voltage, each battery group is tested for charge and discharge cycles, and the capacity, internal resistance change and temperature change of each cycle are recorded.
[0094] Pay special attention to observe and record the temperature rise of the battery during charging, and whether there are any signs of thermal runaway such as abnormal sounds, odors or deformation.
[0095] The test results are as follows:
[0096] 1. Basic performance test results
[0097] Under standard charging conditions (4.2V), all 75 (15 groups, 5 in each group) battery samples were tested for initial capacity and internal resistance. The following are the detailed test results:
[0098]
[0099]
[0100] 2. Test under high voltage
[0101] Perform charge and discharge cycle tests on each battery group, and record the capacity, internal resistance change and temperature change of each cycle.
[0102] The batteries numbered 1-15 were tested at a charging voltage of 4.5V, and the results are as follows:
[0103]
[0104]
[0105] The batteries numbered 1-15 were tested at a charging voltage of 4.6V, and the results are as follows:
[0106]
[0107]
[0108]
[0109] The batteries numbered 1-15 were tested at a charging voltage of 4.7V, and the results are as follows:
[0110]
[0111] The batteries numbered 1-15 were tested at a charging voltage of 4.8V, and the results are as follows:
[0112]
[0113]
[0114] For the above experimental results:
[0115] Initial capacity As the charging voltage increases, the initial capacity of all numbered batteries increases. Increasing the charging voltage can increase the battery capacity, but it also increases the thermal load and potential safety risks of the battery.
[0116] At 4.5V and 4.6V charging voltages, the capacity retention rate of the battery after 10 and 50 cycles is high, and the capacity retention rate of most batteries after 50 cycles is still above 90%. However, when the charging voltage is increased to 4.7V and 4.8V, although the initial capacity increases further, the capacity decay rate after the cycle is accelerated, especially after 100 cycles (4.8V test), the capacity retention rate drops significantly.
[0117] All batteries experience an increase in internal resistance as the number of cycles increases. This is a normal phenomenon in the battery aging process, but the increase in internal resistance will affect the performance and efficiency of the battery.
[0118] Under the same number of cycles, the higher the charging voltage, the more obvious the increase in the internal resistance of the battery. This indicates that high-voltage charging will accelerate the degradation of the internal structure of the battery, causing the internal resistance to rise rapidly.
[0119] As the charging voltage and the number of cycles increase, the temperature of the battery also rises accordingly. Especially at high voltage, the temperature rise of the battery during the cycle is more significant. The temperature rise problem caused by high-voltage charging puts higher requirements on the battery's thermal management system. If the thermal management is not good, it may cause battery overheating, thermal runaway and even safety accidents.
[0120] Synergistic stability improvement of 1,3-divinyltetramethyldisiloxane and lithium acesulfame under high voltage charging
[0121] With the increasing application of lithium-ion batteries in electric vehicles, portable electronic devices, and large-scale energy storage systems, the requirements for battery performance are also getting higher and higher. Especially under high-voltage charging conditions, the cycle stability, thermal stability, and safety of the battery have become key factors restricting its development. In order to meet these challenges, researchers are constantly exploring new electrolyte additives in order to improve the performance of batteries under high voltage. Among them, 1,3-divinyltetramethyldisiloxane (1,3-divinyltetramethyldisiloxane) and lithium acesulfame (lithium acesulfame) as electrolyte additives have shown significant synergistic effects and effectively improved the stability of the battery under high-voltage charging conditions. This article will combine experimental data to deeply explore the mechanism of action of these two additives and the principle of their synergistic effect.
[0122] 1,3-Divinyltetramethyldisiloxane is a siloxane compound containing active vinyl groups, which has good thermal and chemical stability. In the electrolyte, 1,3-Divinyltetramethyldisiloxane mainly works through the following mechanisms:
[0123] 1,3-Divinyltetramethyldisiloxane can form a dense passivation film on the surface of the positive electrode material, effectively preventing the direct contact between the electrolyte and the positive electrode material and reducing the occurrence of side reactions. This passivation film can not only inhibit the dissolution of transition metals and prevent the destruction of the positive electrode structure, but also improve the electrochemical stability of the positive electrode material, thereby extending the cycle life of the battery.
[0124] During the first charge process, 1,3-divinyltetramethyldisiloxane can participate in the formation of the solid electrolyte interface (SEI) film, making the SEI film more uniform and dense. The SEI film is a protective film formed between the electrolyte and the negative electrode material during the first charge process, which can prevent further reaction between the electrolyte and the negative electrode material and reduce the decomposition and consumption of the electrolyte. The addition of 1,3-divinyltetramethyldisiloxane makes the SEI film more stable, thereby improving the coulombic efficiency and cycle life of the battery.
[0125] The addition of 1,3-divinyltetramethyldisiloxane can also improve the viscosity, conductivity and wettability of the electrolyte. The reduction in viscosity helps the flow of the electrolyte and the transmission of ions, thereby increasing the reaction rate of the battery; the increase in conductivity can reduce the internal resistance of the battery, improve the battery's charge and discharge efficiency and power density; the improvement in wettability helps the electrolyte to better contact the electrode material, thereby improving the battery's energy conversion efficiency.
[0126] Lithium acesulfame is an organic lithium salt with high ionic conductivity and excellent thermal and chemical stability. In the electrolyte, lithium acesulfame works mainly through the following mechanisms:
[0127] The negative ions of lithium acesulfame are composed of highly electronegative nitrogen (N) atoms and two sulfur (S) atoms with strong electron-withdrawing groups. This structure makes it easier for positive and negative ions to dissociate, thereby significantly improving the ionic conductivity of the electrolyte. High ionic conductivity helps reduce the internal resistance of the battery and improve the battery's charge and discharge efficiency and power density.
[0128] Lithium acesulfame has high electrochemical stability and can match high-voltage cathode materials, broadening the electrochemical window of the battery. This enables the battery to operate at a higher voltage, thereby increasing the battery's energy density and specific capacity.
[0129] The addition of lithium acesulfame can reduce the side reactions between the electrolyte and the electrode materials, and reduce the decomposition and consumption of the electrolyte, which helps to extend the cycle life of the battery and improve the safety and reliability of the battery.
[0130] As electrolyte additives, 1,3-divinyltetramethyldisiloxane and lithium acesulfame showed significant synergistic effects in improving the stability of batteries under high-voltage charging conditions.
[0131] The passivation film formed by 1,3-divinyltetramethyldisiloxane on the surface of the positive electrode can effectively prevent the direct contact between the electrolyte and the positive electrode material and reduce the occurrence of side reactions. Lithium acesulfame improves the ionic conductivity of the electrolyte, reduces the internal resistance of the battery, and improves the charging and discharging efficiency and power density of the battery. The synergistic effect of the two enables the battery to exhibit better cycle stability and thermal stability at high voltage. Specifically, the passivation film formed by 1,3-divinyltetramethyldisiloxane reduces the dissolution and structural damage of the positive electrode material, while lithium acesulfame improves the ion transfer efficiency of the electrolyte and reduces the internal resistance and temperature rise of the battery. This synergistic effect helps to extend the cycle life of the battery and improve the energy density of the battery.
[0132] The addition of 1,3-divinyltetramethyldisiloxane can participate in the formation of the SEI film, making the SEI film more uniform and dense, thereby improving the coulombic efficiency and cycle life of the battery. Lithium acesulfame has high electrochemical stability, can match high-voltage positive electrode materials, and broaden the electrochemical window of the battery. The synergistic effect of the two enables the battery to operate at a higher voltage while maintaining good cycle stability and safety. Specifically, the stable SEI film formed by 1,3-divinyltetramethyldisiloxane can prevent further reaction between the electrolyte and the negative electrode material, reducing the decomposition and consumption of the electrolyte; while lithium acesulfame widens the electrochemical window of the battery, allowing the battery to operate at a higher voltage without side reactions. This synergistic effect helps to improve the energy density and specific capacity of the battery.
[0133] The addition of 1,3-divinyltetramethyldisiloxane and lithium acesulfame can also synergistically improve the viscosity, conductivity and wettability of the electrolyte. The addition of 1,3-divinyltetramethyldisiloxane can reduce the viscosity of the electrolyte, improve the fluidity of the electrolyte and the ion transmission efficiency; while lithium acesulfame can increase the conductivity of the electrolyte and reduce the internal resistance of the battery. The synergistic effect of the two makes the electrolyte more suitable for high-voltage charging conditions, which helps to improve the charge and discharge efficiency and power density of the battery. At the same time, the addition of 1,3-divinyltetramethyldisiloxane and lithium acesulfame can also improve the wettability of the electrolyte, allowing the electrolyte to better contact with the electrode material and improve the energy conversion efficiency of the battery.
[0134] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An electrolyte for a ternary positive electrode secondary battery, for a secondary battery whose positive electrode active material is LiNixCoyMnzO2, wherein x, y, z represent the molar fractions of nickel, cobalt, and manganese, respectively, and x+y+z=1, and the electrolyte comprises carbonate, ethyl propionate, and lithium salt, characterized in that Also included are silicone additives and lithium acesulfame additives.
2. The electrolyte according to claim 1, characterized in that The carbonate is a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC), and the mass ratio of EC to EMC is 3-4:7-6.
3. The electrolyte according to claim 1 or 2, characterized in that The mass ratio of the ethyl propionate in the electrolyte is 1-2%.
4. The electrolyte according to any one of claims 1 to 3, characterized in that The lithium salt is LiPF6, and its mass fraction in the electrolyte is 13% to 15%.
5. The electrolyte according to any one of claims 1 to 4, characterized in that The organic silicon additive is 1,3-divinyltetramethyldisiloxane (DTMS), and its mass fraction in the electrolyte is 0.1% to 0.5%.
6. The electrolyte according to any one of claims 1 to 5, characterized in that The mass fraction of the lithium acesulfame in the electrolyte is 0.1% to 1%.
7. The electrolyte according to any one of claims 1 to 6, characterized in that The electrolyte also meets the following conditions: the electrolyte is suitable for nickel-cobalt-manganese ternary lithium batteries with a charging voltage of 4.5V to 4.8V.
8. The electrolyte according to any one of claims 1 to 7, characterized in that The positive electrode active material of the secondary battery is NCM811.
9. The electrolyte according to any one of claims 1 to 8, characterized in that The electrolyte injection coefficient is 3.15-3.5 g / Ah.
10. A secondary battery, characterized in that Include: A positive electrode, the positive electrode comprising an active material LiNixCoyMnzO2, wherein x, y, z represent the molar fractions of nickel, cobalt, and manganese, respectively, and x+y+z=1; A negative electrode comprising graphite as an active material; The electrolyte comprising the electrolyte of claims 1 to 9, The secondary battery has good cycle stability and capacity retention rate when the charging voltage is 4.5V to 4.8V.
Citation Information
Cited By
Lithium ion battery
CN121507103A